Breaking the habit: Does fracturing your wrist change your travel and driver behaviour?. (April 2016) - Musselwhite, Charles B.A.; Calcraft, Melissa J.; Roberts, Matthew; Fox, Rebecca; Swinkels, Annette; Turton, Pat; Young, Sue
Highlights: 18% of participants drove during the time they had a forearm plaster cast on. Those that drove reported that wearing a plaster cast did not reduce driver safety. Participant's use of buses and trains, walking and taking lifts all increased. Participant's travelled fewer miles but made more journeys. Information provision did not affect whether someone decided to drive or not. Abstract: When someone breaks their wrist it presents a disruption to everyday routine. Some of this is as a result of having to change travel patterns. This paper investigates the changes people make to their travel behaviour in the light of an unexpected change in their situation caused by fracturing their wrist and wearing a forearm plaster cast. One hundred and eleven participants, approached as they were having their plaster cast removed, completed a questionnaire addressing travel behaviour change, driver safety and information provision covering their time in a plaster cast (typically an average of 5–6 weeks). Eighteen percent of participants drove during the time they had a forearm plaster cast on. All reported they felt safe in doing so and that wearing the plaster cast did not compromise safety, though it was uncomfortable and compensatory behaviours took place. Risk and affective scales did not predict whether participants drove in a cast, suggesting that practical and utilitarian, rather than psychosocial, reasons were the motivation for driving in a plaster cast. Eighty-two percent found other ways of travelling without using their car. Participant's use of buses and trains, walking and taking lifts were all increased and overall, across all modes of transport, participants travelled fewer miles but made more journeys. There was a reduction in cycling, especially for those who drove in a cast, suggesting cyclists who broke their wrist changed to driving while their arm was in a cast. Information provision did not affect whether someone drove or not. Implications for providing travel information to help people avoid car use while their forearm is in a cast and maintaining behaviour change afterwards are discussed.